Sustainable communication for MSMEs in Kampung Laos: Study on the digital economic empowerment of villages - Lishapsari Prihatini; Sumarni Bayu Anita; Siti Lady Havivi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
This research examines sustainable communication practices in the digital economic empowerment of MSMEs in Kampung Laos, Merah Mata Village, Banyuasin Regency, South Sumatra. Although the digitalization of MSMEs is often understood as a matter of technology adoption, there is still limited research that places communication, local values, and power relations as the foundation for the sustainability of the digital economy in rural communities. This research uses a qualitative approach with a participatory case study design. Data was collected through participant observation in university-community engagement programs, in-depth interviews with purposively selected key informants (farmers, MSME actors, village officials, and institutional representatives), and a review of CSR documents and community production archives. The research findings identify four main dimensions of sustainable communication, namely, local narrative-based social marketing in “Kampung Laos,” CSR support as an initial trigger for empowerment, community participation in collective decision-making, and low-digital technology adaptation through WhatsApp and Instagram. This practice increases product visibility and order flow stability, although it still faces limitations in digital literacy and distribution. This study shows that digital economic empowerment lies on a spectrum between independence and dependence on external actors. This research contributes to the development of sustainable communication studies by affirming that integrating local values, social innovation, and participatory communication is more crucial for the economic sustainability of MSMEs in the digital age than simply adopting technology.